Nose-clip use in semi-free ranging pigs reduces rooting without disrupting affiliative behaviour or causing prolonged stress - E. Collarini; O. Dal Monte; M. Traversa; E. Mecarelli; C. Medana; S. Visentin; G. Cordoni; I. Norscia (Animal, 2025)
Domestic pigs (Sus scrofa) raised under natural conditions can show their complete behavioural repertoire. However, rooting behaviour can have a great impact on the environment. In the context of the promotion of farm animal welfare and environmental concerns, this study investigated the potential of nose-clips as a less invasive alternative to nose-rings for the management of rooting behaviour of free-ranging pigs. We collected behavioural data and salivary cortisol levels on two groups: an experimental group (n = 17) with nose-clips and a control group (n = 17) without nose-clips. After the nose-clipping, we observed a temporary increase in anxiety-related behaviour and cortisol levels during the 1st week, followed by a return to pre-application levels in the following weeks. We found a temporary decrease in affiliative interactions involving the nose during the 1st week after the application of nose-clips, whereas no differences in affiliative interactions without nose contact and aggression levels were observed. Moreover, nose-clips effectively reduced destructive excavation behaviours, without leading to a simultaneous increase in other exploratory behaviours. In conclusion, our findings show that nose-clips could be a solution that mitigates destructive rooting while preserving social interactions and animal welfare. Further research is essential to consolidate these findings and assess the long-term implications of this approach.